2003
DOI: 10.1063/1.1628828
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of giant magnetoimpedance effect of electroplated NiFe/Cu composite wires by dc Joule annealing

Abstract: The influence of dc Joule annealing of electroplated Ni80Fe20/Cu composite wires on their giant magnetoimpedance (GMI) effect is presented in this article. Successive thermal treatments by dc Joule annealing with the current density ranging from 2.4 to 9.6×108 A/m2 were applied to the composite wires for a fixed annealing time of 1 min to release the residual stresses in the plated NiFe layer. The results showed that the magnetoimpedance (MI) effect of the composite wires can be greatly enhanced by dc Joule an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…Current annealing owing to generating circumferential magnetic field and Joule heating can release internal stresses, induce anisotropy and grow crystal grains. Improvement of MI properties in NiFe/Cu microtubes by proper choice of dc annealing parameters has been reported by some authors [5,12]. In this work, we investigate the influence of ac-dc Joule annealing on GMI response of NiFe/Cu microtubes.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Current annealing owing to generating circumferential magnetic field and Joule heating can release internal stresses, induce anisotropy and grow crystal grains. Improvement of MI properties in NiFe/Cu microtubes by proper choice of dc annealing parameters has been reported by some authors [5,12]. In this work, we investigate the influence of ac-dc Joule annealing on GMI response of NiFe/Cu microtubes.…”
mentioning
confidence: 92%
“…Heterogeneous materials reveal a superior GMI response than homogeneous materials. It has been shown that among the samples with the same magnetic characteristics, the composite tubes can show the highest magnetoimpedance effect [5]. The origin of GMI in composite microtubes unlike the homogeneous materials does not lie in classical skin effect, and variation in the penetration depth induced by the applied static magnetic field plays no direct role.…”
mentioning
confidence: 99%
“…In previous study [13,22], GMI effect can be enhanced by Joule annealing which induces circumferential magnetic domain. The corresponding annealing current ranges from several hundred milliamperes to several amperes.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the composite wires were fabricated by magnetron sputtering [11], electroplating [12][13][14][15][16], chemical plating [17], or MEMS technique [18]. However, the GMI sensitivity of the composite wires is not high since their magnetic structure cannot be well controlled by these methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation